If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 3(2 + -2x) = 9 7 + (2 * 3 + -2x * 3) = 9 7 + (6 + -6x) = 9 Combine like terms: 7 + 6 = 13 13 + -6x = 9 Solving 13 + -6x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -6x = 9 + -13 Combine like terms: 13 + -13 = 0 0 + -6x = 9 + -13 -6x = 9 + -13 Combine like terms: 9 + -13 = -4 -6x = -4 Divide each side by '-6'. x = 0.6666666667 Simplifying x = 0.6666666667
| .06x+1.7=-0.44x+3 | | 100/18.75 | | 4a/15y*5y/2a^3y^2 | | 0.58/x=0.15/0.3 | | 5x-4=4+3x+3 | | 525+21m=850 | | (x^2-y^2)dx+(y^2-2xy)dy=0 | | (4y-9)(4-y)=0 | | 2x-1y+10z= | | (5/3)x-3/4=7/12 | | 5x+5y+6z-3x+4z-6y= | | 100+8.00h=10.00h | | c=5/9(104-32) | | p=2g+2mforg | | 4x^2-2x-26=0 | | 2x+100=272 | | 6k-18=12-4k | | 2p-8=4-4p | | 2y+3(y-6)=7y-4(y-10) | | 2p-8=13-5n | | 2x-7/4+x=2x+7/2+5 | | 7-4a=5a-20 | | 2x+10=14+3x+3 | | 2x-7/4 | | 3n-27=13-5n | | 0.9x-14=1.7x-18 | | 2x+10=14+3 | | 10x+14=3(3x+4) | | 3n-9=13-5n | | 5x-7y=-9 | | 3x-16= | | -107x-7x=7x+19 |